Substituting whole grains for refined grains in a 6-wk randomized trial favorably affects energy-balance metrics in healthy men and postmenopausal women. Issue 3 (8th February 2017) - Karl, J Philip; Meydani, Mohsen; Barnett, Junaidah B; Vanegas, Sally M; Goldin, Barry; Kane, Anne; Rasmussen, Helen; Saltzman, Edward; Vangay, Pajau; Knights, Dan; Chen, C-Y Oliver; Das, Sai Krupa; et al.
ABSTRACT: Background: The effect of whole grains on the regulation of energy balance remains controversial. Objective: We aimed to determine the effects of substituting whole grains for refined grains, independent of body weight changes, on energy-metabolism metrics and glycemic control. Design: The study was a randomized, controlled, parallel-arm controlled-feeding trial that was conducted in 81 men and postmenopausal women [49 men and 32 women; age range: 40–65 y; body mass index (in kg/m 2 ): <35.0]. After a 2-wk run-in period, participants were randomly assigned to consume 1 of 2 weight-maintenance diets for 6 wk. Diets differed in whole-grain and fiber contents [mean ± SDs: whole grain–rich diet: 207 ± 39 g whole grains plus 40 ± 5 g dietary fiber/d; refined grain–based diet: 0 g whole grains plus 21 ± 3 g dietary fiber/d] but were otherwise similar. Energy metabolism and body-composition metrics, appetite, markers of glycemic control, and gut microbiota were measured at 2 and 8 wk. Results: By design, body weight was maintained in both groups. Plasma alkylresorcinols, which are biomarkers of whole-grain intake, increased in the whole grain–rich diet group (WG) but not in the refined grain–based diet group (RG) ( P -diet-by-time interaction < 0.0001). Beta ± SE changes (ΔWG compared with ΔRG) in the resting metabolic rate (RMR) (43 ± 25 kcal/d; P = 0.04), stool weight (76 ± 12 g/d; P < 0.0001), and stool energy content (57 ± 17 kcal/d; P = 0.003), but not in stool energy density, were higher in the WG. When combined, the favorable energetic effects in the WG translated into a 92-kcal/d (95% CI: 28, 156-kcal/d) higher net daily energy loss compared with that of the RG ( P = 0.005). Prospective consumption ( P = 0.07) and glycemia after an oral-glucose-tolerance test ( P = 0.10) trended toward being lower in the WG than in the RG. When nonadherent participants were excluded, between-group differences in stool energy content and glucose tolerance increased, and between-group differences in the RMR and prospective consumption were not statistically significant. Conclusion: These findings suggest positive effects of whole grains on the RMR and stool energy excretion that favorably influence energy balance and may help explain epidemiologic associations between whole-grain consumption and reduced body weight and adiposity. This trial was registered at clinicaltrials.gov as NCT01902394.